1985
DOI: 10.1113/jphysiol.1985.sp015666
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐dependent inward current in Aplysia bursting pace‐maker neurones.

Abstract: SUMMARY1. Depolarizing voltage-clamp pulses elicit a triphasic series of tail currents (phase I, II and III) in Aplysia burst-firing neurones L2-L6. The sequence and time course of the tail currents resemble slow changes in membrane potential which follow bursts in the unclamped cell.2. The phase II tail current is an inward current with a time course similar to that of the depolarizing after-potential (d.a.p.) which follows bursts in the unclamped cell.The phase II tail current is suppressed by depolarizing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
2

Year Published

1986
1986
2006
2006

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 52 publications
2
96
2
Order By: Relevance
“…The DAPs last for hundreds of milliseconds to seconds and have amplitudes up to 10 mV, depending on the number of preceding spikes and membrane potential levels at which they are evoked (Andrew & Dudek, 1984;Andrew, 1987). Resembling those identified in invertebrate bursting pacemaker neurones (Thompson & Smith, 1976;Kramer & Zucker, 1985a) and other mammalian CNS neurones (Llin as, 1988;White, Lovinger & Weight, 1989), DAPs as well as phasic firing in SON neurones are abolished by depleting extracellular Ca¥, blocking membrane Ca¥ channels or chelating cytosolic free Ca¥ (Inenaga, Akamatsu, Nagatomo, Ueta & Yamashita, 1992;Li et al 1995). Our recent study has further demonstrated that interference with Ca¥-induced Ca¥ release from internal stores, with either blockade of intracellular ryanodine receptors or depletion of internal Ca¥ pools, reduces DAPs and eliminates phasic firing in SON cells (Li & Hatton, 1997).…”
mentioning
confidence: 54%
“…The DAPs last for hundreds of milliseconds to seconds and have amplitudes up to 10 mV, depending on the number of preceding spikes and membrane potential levels at which they are evoked (Andrew & Dudek, 1984;Andrew, 1987). Resembling those identified in invertebrate bursting pacemaker neurones (Thompson & Smith, 1976;Kramer & Zucker, 1985a) and other mammalian CNS neurones (Llin as, 1988;White, Lovinger & Weight, 1989), DAPs as well as phasic firing in SON neurones are abolished by depleting extracellular Ca¥, blocking membrane Ca¥ channels or chelating cytosolic free Ca¥ (Inenaga, Akamatsu, Nagatomo, Ueta & Yamashita, 1992;Li et al 1995). Our recent study has further demonstrated that interference with Ca¥-induced Ca¥ release from internal stores, with either blockade of intracellular ryanodine receptors or depletion of internal Ca¥ pools, reduces DAPs and eliminates phasic firing in SON cells (Li & Hatton, 1997).…”
mentioning
confidence: 54%
“…In each of these cases, activation of the calcium channels contributes a depolarizing current that helps bring the cell to threshold during the bursts. Bursts are terminated by inactivation of the calcium channels (Kramer and Zucker, 1985;Huguenard and Prince, 1992;Bal and McCormick, 1997) or by activation of calciumactivated potassium channels after calcium entry (Wong and Prince, 1978;Del Negro et al, 1999;Golding et al, 1999). In Purkinje neurons, however, P/Q-type calcium channels are responsible for the abrupt termination of each burst by generating a dendritic calcium spike.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the ganglion removal, desheathing, axotomy and solution changes have been previously described (Kramer & Zucker, 1985; Lando & Zucker, 1989). Most experiments were done on axotomized left upper quadrant neurons, particularly L3 and L6 which have been shown to possess a Ca2+-activated K+ conductance (IK(ca)) that is largely abolished by extracellular tetraethylammonium (TEA+) ions (Deitmer & Eckert, 1985).…”
Section: Methodsmentioning
confidence: 99%
“…Details of the two-electrode voltage clamp technique employed have been previously described (Smith & Zucker, 1980; Kramner & Zucker, 1985). In all Ica experiments, the voltage and current electrodes were filled with 3 M CsCl and had resistances of 1-5 MCI.…”
Section: Voltage Clampmentioning
confidence: 99%